O PAPEL DO MITO NAS NARRATIVAS ORAIS DOS KAINGANG NA BACIA DO LAGO GUAÍBA, PORTO ALEGRE, RS - Petry, Lívia; Tettamanzy, Ana Lúcia; Freitas, Ana Elisa de Castro (Organon, 2007)
This study deals with the mythical dimension of the Kaingang oral narratives, a Jê Meridional society whose traditional territories are located in the south of Brazil. It is based on interviews carried out among Kaingang communities located in the hydrographic region of the Guaíba Lake basin, Rio Grande do Sul state, analyzed in view of the native etnology and of the myth theory. It was considered specially the studies of Egon Schaden (1913) and Mircea Eliade (1963), completed by the studies of Robert Crèpeau (1997), Rogério Reus Gonçalves da Rosa (1998) and Sérgio Baptista da Silva (2002). The preliminary data allow to recognize that the Kamé-Kairukré cosmologic dualism, revealed in the version of the myth of the Kaingang origin collected by Telêmaco Borba (1908), remains as a wire coductor of the contemporary Kaingang thought, orienting its narratives, its history and nature conceptions, its life in society and its duty notion.